Análise da inserção da educação ambiental no volume I do currículo do 6° ano/5ª série do ensino fundamental do estado de São Paulo - Timoteo, Camila Kwiatkoski (2016)
The current environmental situation is a worrying scenario, making it inevitable to take different measures that result in solutions that overcome social and environmental challenges, pointing to a world of sustainable societies. As an important part of the complex and articulated group of necessary measures, education is essential, since it is capable of raising awareness that mobilizes people for social transformation. Environmental education is a practice that incorporates themes that are crucial in the society development in general and, if implemented in a critical, reflexive, transformative and emancipatory perspective, can increase the power of people action in this direction, favoring the challenging inflection, now in demand. In Brazil, this practice is referred to in concepts and principles known and established, which must be followed in its exercise, in projects and programs of community interaction, or in contents worked in the school environment. In this context, based on an evaluation of the National Curriculum Parameters of the Environment Transversal Theme and the National Curriculum Guidelines in Environmental Education, this paper defined four indicators for the analysis of the the São Paulo State official curriculum of the elementary education in relation to the approach to the environmental question: knowledge, participation, values, contextualization. Bibliographic review followed by documental analysis were the procedures used in the research, complemented by surveys of empirical researches to verify the occurrence of environmental education initiatives in the hidden curriculum in school practices. From the documental analysis of the Teacher's Notebook of all disciplines, we sought, among the description of the activities proposed there, to verify the occurrence of the different indicators. It was observed that environmental education practice is still restricted mainly to the areas of Science and Geography, which contrasts with the main indication, parameters and guidelines established, that this should be a practice that transcends the curriculum, pointing to a possible interdisciplinarity. We made suggestions for insertion of the environmental theme in different situations of its absence in the materials analyzed, trying to show concretely possibilities of approaching the environmental issue in all disciplines.